GROWTH, YIELD AND QUALITY PERFORMANCE OF COTTON CULTIVAR BH-160 (Gossypium hirsutum L.) AS INFLUENCED BY DIFFERENT PLANT SPACING - A. U. H. Ahmad; R. Ali; S. I. Zamir; N. Mahmood (Journal of Animal and Plant Sciences, 2009)
A field experiment was carried out in District Toba Tek Singh to evaluate the effect of plant spacing on growth, yield and quality of cotton variety BH-160 (Gossypium hirsutum L.). The treatments comprised of four plant spacing’s viz. 15 cm, 22.5 cm, 30 cm and 37.5 cm. The experiment was laid out in randomized complete block design (RCBD) by using four replications. The data exhibited that plant spacing significantly influenced number of sympodial branches per plant, plant height (cm), number of bolls per plant, average boll weight (g), seed cotton yield per plant (g) and seed cotton yield (kg ha-1) while number of monopodial branches per plant, ginning out turn (%), fibre length (mm) and fibre fineness (μg inch-1) were affected non significantly by plant spacing. It is suggested that for the purpose of getting higher seed cotton yield per hectare the farmers should adopt the practice of growing cotton crop in general and particularly the variety BH-160 at plant spacing of 22.5 cm x 75 cm.
Keywords: Growth; Quality; Cotton